Kajian Terhadap Pejabat Pembuat Akta Tanah Sebagai Pejabat Umum Pembuat Akta Otentik Dalam Peralihan Hak Atas Tanah - , FITRISIA PARAMITHA U ([Yogyakarta] : Universitas Gadjah Mada, 2014)
A research entitled âA Study On PPAT (The Official Empowered To Draw Up Land Deed) As Public Official Empowered To Draw Up Authentic Deed In The Transfer Of Land Titleâ is aimed at understanding, examining and analyzing the legal status of deed drafted by PPAT in the law of evidence as well as understanding, analyzing and examining the status of PPAT as the official draws up the deed in the transfer of land title. This research was conducted through normative-juridical approach giving top priority to secondary data consists of primary, secondary, and tertiary legal material. This research was equipped with primary data to sharpen the analysis. The secondary data was collected through documented study and later equipped with direct interviews with resource persons. Afterward, the data collected was analyzed qualitatively. Based of the research results, it was recognized that a deed drawn up by PPAT is a product from public official, as an evidence of legal action concerning the transfer of land title which is used in the requirement of land registration. Deed drawn up by PPAT is an authentic deed according to Article 1868 of Civil Code. The form of the deed was standardized and made by the third party (government). PPAT deed has status as absolute and binding evidence. The position of PPAT is public official as stipulated in Article 1 No. 4 UUHT in conjunction with Article 1 No. 24 Government Regulation Number 24 Year 1997 in conjunction with Article 1 No. 1 Government Regulation Number 37 Year 1998. The authority of PPAT in drawing up land deed is an authority attached in PPAT official. PPAT was emerged directly from the policy rules of government, and PPAT is not the subordination of National Defense Bureau. The affiliation of PPAT and National Defense Bureau is equal and the same, in which PPAT and National Defense Bureau has its own functions and roles in the process of land registration. PPAT or Notary Organization should have dynamic role to synchronize National Defense Bureau and PPAT Notary to smoothen the process of land registration. Keywords: PPAT, PPAT deed, Public Official